2017
DOI: 10.1016/j.cortex.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the body schema on mirror-touch synesthesia

Abstract: Individuals with mirror-touch synesthesia (MTS) report feeling touch on their own body when seeing someone else being touched. We examined how the body schema - an on-line representation of body position in space - is involved in mapping touch from a viewed body to one's own body. We showed 45 mirror-touch synesthetes videos of a hand being touched, varying the location of the viewed touch by hand (left, right), skin surface (palmar, dorsal) and finger (index, ring). Participant hand posture was either congrue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…For instance, stimuli depicting pain or threatening touch experiences, such as a knife tip touching a face, have been shown to elicit more frequent and intense vicarious responses compared to stimuli showing touch with non-threatening objects like a fingertip or feather (Holle et al, 2011; Ward et al, 2018; Ward and Li, 2022). Apart from emotional factors, research has also shown that physical aspects like congruent body posture and the viewer’s perspective can modulate vicarious sensory perception (Holle et al, 2011; Medina and DePasquale, 2017). Studies often incorporate a wide range of visual touch stimuli that vary in perceived arousal and threat, the body part touched, hedonic qualities, viewing perspective, and the plausibility of the visual cue (e.g., touch to an upright face versus an inverted one).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, stimuli depicting pain or threatening touch experiences, such as a knife tip touching a face, have been shown to elicit more frequent and intense vicarious responses compared to stimuli showing touch with non-threatening objects like a fingertip or feather (Holle et al, 2011; Ward et al, 2018; Ward and Li, 2022). Apart from emotional factors, research has also shown that physical aspects like congruent body posture and the viewer’s perspective can modulate vicarious sensory perception (Holle et al, 2011; Medina and DePasquale, 2017). Studies often incorporate a wide range of visual touch stimuli that vary in perceived arousal and threat, the body part touched, hedonic qualities, viewing perspective, and the plausibility of the visual cue (e.g., touch to an upright face versus an inverted one).…”
Section: Introductionmentioning
confidence: 99%
“…Although the visuo-tactile interference task of Banissy and Ward (2007) has been shown to offer a good way of identifying people with MTS, it requires bespoke equipment that is not readily accessible and requires different labs to establish their own baseline measures (tailored to their own equipment). An alternative approach that we (Holle, Banissy, Wright, Bowling, & Ward, 2011) and others (e.g., Baron-Cohen et al, 2016;Medina & De Pasquale, 2017) have used is to present participants with movies depicting touch and note the frequency and/or intensity of any felt tactile sensations. But how many tactile sensations need to be reported to meet the criteria for having MTS-one stimulus, all stimuli, or somewhere in between?…”
Section: Introductionmentioning
confidence: 99%
“…While existing literature has provided valuable insights, it has often directed its focus towards a specific group known as 'mirror-touch synesthetes'. This small subset of individuals reportedly experiences vicarious sensations in a manner distinct from the broader population (Holle et al, 2011;Ioumpa et al, 2019;Li et al, 2022;Medina and DePasquale, 2017;Ward et al, 2018;Ward and Li, 2022). The aim of our exploratory study was to investigate the characteristics of reported vicarious sensations in a large sample of naïve undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies employed a broad range of stimuli varying in aspects like arousal, threat, valence levels, the specific body part touched, viewing perspective, and stimulus plausibility (e.g., upright vs. inverted face). While some research has examined the influence of factors like body posture on reported sensations (Holle et al, 2011; Medina and DePasquale, 2017), there are other nuances that require further exploration for a comprehensive understanding of their effects. For example, evidence suggests that stimuli portraying painful events may be more likely to elicit vicarious responses (Ward et al, 2018; Ward and Li, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation